THE EFFECT OF FERMENTED OIL PALM FRONDS IN DIET ON BODY WEIGHT GAIN AND MEAT QUALITY OF GOAT - Musnandar, E.; Hamidah, A.; Muthalib, R.A. (Diponegoro University, 2011)
The aims of study were to evaluate the use of fermented of oil palm fronds (FOPF) on body weightgain and meat quality of goat. This experiment was arranged in Completely Randomized Design with 3treatments i.e. R1 (grass 0%: FOPF 100%), R2 (grass 50%: FOPF 50%) and R3 (grass 100%: FOPF 0%)and 5 replications. The parameters of the study were feed intake, average daily gain (ADG), weight andpercentage of carcass and meat quality. The results indicated that feed intake and meat quality of goatwas not affected by treatment, but the average daily gain, carcass weight, and percentage of carcass, wasaffected by the differences of percentage of FOPF in the pellet complete feed. The best ration was in theR1 ration (grass 0%: FOPF 100%) that significantly different (P<0.05) from the other rations. The feedintake tended to be higher in goat fed R1 (895.87 g/d) compared to those in goat with the R2 (854.38g/d) and R3 (851.53 g/d). The average daily gain and carcass weight were higher in goat fed R1 rationcompared to those in goat fed R2 and R3. Consequently, the carcass percentage in R1 was higher thanthose in R2 and R3. The carcass percentage was ranged from 38.41-41.38%. The Ribeye area was higherin goat fed R1 (9.73 cm2) than R2 (8.34 cm2) and R3 (7.76 cm2). In this study, the protein content ofgoat meat was ranged from 19.06 to 20.71%, lipid content was ranged from 0.703 to 1.106% and watercontent was range from 72.45% to 74.12%, in which were not different among the treatments. It can beconcluded that the use of FOPF in a complete feed could improve performance and meat quality of goat.